Assessment of Adequacy of Product Appearance Attributes to the Design Objective - Andrei DUMITRESCU (Management and Economics Review)
A new method for assessment of product aesthetics („Assessment of adequacy of product appearance attributes to the design objective and to values of market segment”, Adequacy Method, in short) was developed by the author. The method is based on the need to assess product aesthetics against the design objective and the human values / goals of the target market segment. In a pre-test, eight products (from four classes) with the most different design were chosen for testing the method. Then, in an experimental study, the products were assessed using the proposed method by students from a technical university. After statistically analysing the assessment results, it was found that the method criteria and the method itself proved to be reliable, efficient, and clear. The proposed method was also tested by comparison with a complex method (FTESE – Functional, Technical, Ergonomic, Significance and Esthetic Analysis). The same products used in the paper presenting the FTESE method were assessed using the proposed method and lead to the same ordering of products according to their aesthetics. But the comparison also indicated that the proposed method allows for a superior refinement.